Featured Cover. (14th November 2021) - Yoshioka, Hideki; Noguchi, Takafumi; Kobayashi, Kyoichi; Kanematsu, Manabu; Ando, Tatsuo; Pareek, Sanjay; Hayakawa, Tetsuya
Abstract : JohanssonThe cover image is based on the Original Article Development of a New Intermediate‐scale Box Test on Sandwich Panel Products Compared with ISO 13784‐1 Room Test and EN 13501‐1 Classification System by Hideki Yoshioka et al., https://doi.org/10.1002/fam.2984 .